2014
DOI: 10.1038/onc.2013.597
|View full text |Cite
|
Sign up to set email alerts
|

Selective killing of lung cancer cells by miRNA-506 molecule through inhibiting NF-κB p65 to evoke reactive oxygen species generation and p53 activation

Abstract: The tumor suppressor p53, nuclear factor-κB (NF-κB) and reactive oxygen species (ROS) have crucial roles in tumorigenesis, although the mechanisms of cross talk between these factors remain largely unknown. Here we report that miR-506 upregulation occurs in 83% of lung cancer patients (156 cases), and its expression highly correlates with ROS. Ectopic expression of miR-506 inhibits NF-κB p65 expression, induces ROS accumulation and then activates p53 to suppress lung cancer cell viability, but not in normal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 59 publications
6
59
0
Order By: Relevance
“…Upregulation of miR-506 occurs in 83% lung cancer, however, miR-506 is considered as a tumor suppressor instead of an oncomir. It is known that miR-506 negatively regulates NF-κB p65 expression and thus increases ROS production, which, in turn, activates p53 to kill cancer cells through increased apoptosis (76). …”
Section: Micrornas Regulate Ros Productionmentioning
confidence: 99%
“…Upregulation of miR-506 occurs in 83% lung cancer, however, miR-506 is considered as a tumor suppressor instead of an oncomir. It is known that miR-506 negatively regulates NF-κB p65 expression and thus increases ROS production, which, in turn, activates p53 to kill cancer cells through increased apoptosis (76). …”
Section: Micrornas Regulate Ros Productionmentioning
confidence: 99%
“…Recently, it has been reported that miR-506 inhibits epithelial mesenchymal transition (EMT) in ovarian cancer and breast cancer [10,11] . In addition, miR-506 can significantly restrain the proliferation of lung cancer cells [12] . All these reports suggest that miR-506 is a novel microRNA that is important in the development of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was demonstrated that miR-506 functions as a tumor suppressor in neuroblastoma by directly targeting ROCK1. Previous studies have reported that the expression of miR-506 is reduced in numerous types of cancer, including epithelial ovarian cancer (15)(16)(17)(18), hepatocellular carcinoma (19), cervical cancer (20), lung cancer (21), breast cancer (22) and colon cancer (23), and is involved in cancer progression, notably cell proliferation, metastasis and apoptosis. In the current study, it was observed that miR-506 was decreased in neuroblastoma tissues and cell lines when compared to normal tissues, supporting the notion that miR-506 functions as a potential tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%